Early screening of thalassemia in pregnant women in northern China by capillary electrophoresis for the determination of hemoglobin electrophoresis: Hemoglobin in anemic pregnant women in northern China - Lin, Meilin; Meng, Yanan; Wang, Yan; Zheng, Hailiang; Liang, Shuxing; Zhao, Qianying; Zhong, Liying; Yan, Shuai (Cellular and Molecular Biology, 2023)
The objective of this study was to analyze the effectiveness of capillary electrophoresis detection of hemoglobin electrophoresis (HE) for the early screening of thalassemia. In the first choice, 974 pregnant women were selected for capillary electrophoresis to detect HE, which showed that 46 of them were abnormal (4.72%), including 16 cases with HbA2<2.5% and 28 cases with HbA2>3.5% and/or HbF≥2.0%. In one case each of HbH and HbBart’s abnormal bands was found. The genotype test results showed the presence of thalassemia in 34 cases, using the genotype test results as the gold standard, after calculation it was seen that capillary electrophoresis for HE diagnosis of the occurrence of thalassemia had a sensitivity and specificity of 54.34% and 70.97% (P<0.05). These results suggest that in the screening of thalassemia in northern China, capillary electrophoresis for HE has good application and can be used as one of the routine screening tools, but further confirmation by genotype testing is still needed.